Republic of Moldova Food Security Assessment - World Bank (Washington, DC, 2015)
This report provides an analysis of food security in Moldova. It attempts to outline the specific characteristics of food insecurity found in Moldova and to identify its underlying causes. This report provides a basis on which sound public policy can be built. The understanding of food security as a concept has evolved in Moldova over time, but policy has remained focused on food availability as the primary attribute of food security. The report looks at how many people are food insecure in Moldova, where these people live, who they are, and why they face food security challenges. The report adopts the international food security concept and analytical framework based on the four key dimensions: (i) the availability of food; (ii) access to food; (iii) utilization of food; and (iv) the stability of these three dimensions over time. The report is divided into following parts. The part one outlines the methodology used and provides a brief overview of Moldovas agriculture sector. In part two the report focuses on overall food security outcomes by assessing how many people are food insecure in Moldova, where do they live, who they are, and when is food security most affecting them. Part three provides a comprehensive analysis of the four dimensions of food security (availability, access, utilization, and stability) and identifies bottlenecks. Part four introduces the institutional actors and the policy framework. The report concludes with policy recommendations.